2020
DOI: 10.1007/s10973-020-09526-w
|View full text |Cite
|
Sign up to set email alerts
|

Thermoanalytical and dilatometric studies of the Al2O3–Cu–Mo hybrid composite

Abstract: The present research is focused on the characterization of the composites from Al 2 O 3-Cu-Mo system. The composites were prepared by slip casting method and subsequent sintering of green bodies in a reduced atmosphere. Two series of samples with different volume content of metallic powders were produced in the work: 10 vol% and 15 vol% of metal content with respect to the total solid-phase content. The sintering process of the composites was analyzed in detail. The linear shrinkage of the composites was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The above sintering curve profile was applied based on previous study findings for this system. [28] III. RESULTS…”
Section: Sample Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…The above sintering curve profile was applied based on previous study findings for this system. [28] III. RESULTS…”
Section: Sample Preparationmentioning
confidence: 99%
“…The authors' previous research shows that to obtain an effective composite molding process and to produce specimens with the appropriate properties, the suspension must be dispersed and stable over time. [28] Studies have shown that suspensions containing 50 vol pct solid content with 10 vol pct and 15 vol pct of metal particles (Cu and Mo) with respect to the total solid-phase content were stable for 24 h from the moment of mass preparation. [28] In this investigation, the sedimentation studies were extended to include another slurry that contained 5 vol pct metallic phase.…”
Section: B Characterization Of Suspension Sedimentationmentioning
confidence: 99%
See 3 more Smart Citations